Clinical implementation of dynamic intensity-modulated radiotherapy: Dosimetric aspects and initial experience - Sivakumar S; Krishnamurthy K; Davis C; Ravichandran R; Kannadhasan S; Biunkumar J; El Ghamrawy Kamal (Journal of Medical Physics, 2008)
This paper describes the initial experience of quality assurance (QA) tests performed on the millennium multi-leaf collimator (mMLC) for clinical implementation of intensity-modulated radiotherapy (IMRT) using sliding window technique. The various QA tests verified the mechanical and dosimetric stability of the mMLC of linear accelerator when operated in dynamic mode (dMLC). The mechanical QA tests also verified the positional accuracy and kinetic properties of the dMLC. The stability of dMLC was analyzed qualitatively and quantitatively using radiographic film and Omnipro IMRT software. The output stability, variation in output for different sweeping gap widths, and dosimetric leaf separation were measured. Dose delivery with IMRT was verified against the dose computed by the treatment planning system (TPS). Monitor units (MUs) calculated by the planning system for the IMRT were cross-checked with independent commercial dose management software. Visual inspection and qualitative analysis showed that the leaf positioning accuracy was well within the acceptable limits. Dosimetric QA tests confirmed the dosimetric stability of the mMLC in dynamic mode. The verification of MUs using commercial software confirmed the reliability of the IMRT planning system for dose computation. The dosimetric measurements validated the fractional dose delivery.